Call for Action to Address Equity and Justice Divide During COVID-19 - Bhaskar, Sonu; Rastogi, Aarushi; Menon, Koravangattu Valsraj; Kunheri, Beena; Balakrishnan, Sindhu; Howick, Jeremy (Frontiers in Psychiatry, 2020)
The coronavirus 2019 disease (COVID-19) is deepening the inequity and injustice among the vulnerable communities. The current study aims to present an overview of the impact of COVID-19 on equity and social justice with a focus on vulnerable communities. Vulnerable communities include, but not limited to, healthcare workers, those from lower socioeconomic backgrounds, ethnic or minority groups, immigrants or refugees, justice-involved populations, and people suffering from chronic diseases or mental illness. The implications of COVID-19 on these communities and systemic disparities beyond the current pandemic are also discussed. People from vulnerable communities’ experience disproportionately adverse impacts of COVID-19. COVID-19 has exacerbated systemic disparities and its long-term negative impact on these populations foretell an impending crisis that could prevail beyond the COVID-19 era. It is onerous that systemic issues be addressed and efforts to build inclusive and sustainable societies be pursued to ensure the provision of universal healthcare and justice for all. Without these reinforcements, we would not only compromise the vulnerable communities but also severely limit our preparedness and response to a future pandemic.